Phonology of Singapore Dabu Hakka - Liaw, Zi Yang (Nanyang Technological University, 2022)
This paper aims to describe the phonological system of the Dabu variety of Hakka Chinese in Singapore. It endeavours to contribute to the description of the various Chinese languages which can be found in Singapore. This was done in an effort to fill the gap in the literature in which descriptions of the Chinese languages in Singapore are lacking. The data for the study were collected from two native speakers of the language. Besides a description of the phonemic inventory of the language, the analysis revealed that it might be possible that the phones [f] and [pʰ] might be undergoing a merge in sound. The asymmetry of [tɕʰ] of not having an unaspirated counterpart in the affricate series of sounds also presents an interesting point of contention. It is hoped that this paper will serve as a foundation for more descriptive work on Dabu Hakka—and by extension, the other Hakka varieties—to be conducted in Singapore by researchers of like mind in the future. Keywords: Dabu Hakka language, Hakka Chinese language, phonology, language documentation, Sinitic, Singapore